2002
DOI: 10.1021/ac0205356
|View full text |Cite
|
Sign up to set email alerts
|

Optical Sensor for Amine Vapors Based on Dimer−Monomer Equilibrium of Indium(III) Octaethylporphyrin in a Polymeric Film

Abstract: A novel transduction chemistry for the development of a polymer film-based optical sensor that responds reversibly to gas-phase amine species at sub-ppm levels is described. The sensor is based on the equilibrium of a indium(III) octaethylporphyrin hydroxide ion-bridged dimer species with corresponding monomeric porphyrins within a thin poly(vinyl chloride) film as a function of the level of volatile amine in the surrounding gas phase. The presence of amines causes the dimeric species to be converted to monome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 56 publications
1
34
0
Order By: Relevance
“…Similar difficulties were observed previously with indium(III), gallium(III), and zirconium(IV) porphyrins as ionophores [9,12,34,35]. Recently, two strategies have been employed to eliminate dimer -monomer chemistry within the sensing membranes and improve overall electrode performance: (1) covalent attachment of the ionophore (In(III) porphyrin) to the polymer matrix [38], and (2) use of a porphyrin ligand with sufficient steric bulk (In(III)-or Ga(III)-picket fence porphyrin) [33].…”
Section: Potentiometric Response Characteristics Of Electrodes Formulsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar difficulties were observed previously with indium(III), gallium(III), and zirconium(IV) porphyrins as ionophores [9,12,34,35]. Recently, two strategies have been employed to eliminate dimer -monomer chemistry within the sensing membranes and improve overall electrode performance: (1) covalent attachment of the ionophore (In(III) porphyrin) to the polymer matrix [38], and (2) use of a porphyrin ligand with sufficient steric bulk (In(III)-or Ga(III)-picket fence porphyrin) [33].…”
Section: Potentiometric Response Characteristics Of Electrodes Formulsupporting
confidence: 84%
“…It has been reported that other group 13 metalloporphyrins (Ga(III) and In(III)) form hydroxy-bridged dimer species [32], and that selective cleavage of these dimers by analyte ions (F À for Ga(III) and Cl À for In(III)) is responsible for the observed non-Nernstian behavior. [33] Indeed, such dimer - monomer chemistry has already been employed to construct optical sensors for chloride [34] and gaseous amines [35] since the dimeric and monomeric forms of the porphyrins exhibit significant differences in their l max for UV-Vis absorption. For the aluminum(III) porphyrin systems reported here, membrane electrodes equilibrated and conditioned with 10 mM fluoride (added to the internal solution, electrodes VIII and XII) display near-Nernstian fluoride response (see Fig.…”
Section: Potentiometric Response Characteristics Of Membrane Electrodmentioning
confidence: 99%
“…It is well known that most membrane electrodes based on metalloporhyrin ionophores have significant response to hydroxide ions [28,29]. Hydroxide has a great affinity to the metal ion center of examined metalloporphyrins (logK F-,OH-= 6.6, 6.9, 7.0 and 7.5 for electrodes 1, 9, 14 and 22 respectively) replacing the counterion of metalloporphyrin when in contact with water [30].…”
Section: The Influence Of Ph On Electrodes Parametersmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] In addition, metal-porphyrin complexes have various functions that are useful in analytical chemistry, and are also of interest to many other researchers, which has led to the use of metal-porphyrin complexes in applications such as optics, 10 chemical stacking, 11 catalysis, 12 electron transport, 13 oxidation-reduction reactions, 14 and biological mimicking substances. 15,16 Thus, numerous reports regarding the chemical function and applications of porphyrin derivatives have been published.…”
Section: Introductionmentioning
confidence: 99%